Are XPD and XPG gene variants related to the mechanism of oral squamous cell carcinoma? - Avci, Hakan; Iplik, Elif Sinem; Aydemir, Levent; Acar, Senol; Kiyak, Erkan; Unur, Meral; Cakmakoglu, Bedia (Cellular and Molecular Biology, 2018)
Oral cavity cancers have anatomically a big part of the body system and include several types of cancer. The aim of the study is to investigate the relation between XPG and XPD gene variants in the DNA repair system and oral squamous cell cancers. A total of 111 patients with a pathologic diagnosis of oral squamous cell carcinoma and a control group of 148 healthy volunteers who presented to Istanbul Faculty of Medicine, Department of Otolaryngology & Head and Neck Surgery and Dentistry Faculty were included in the study. Isolation of DNA was achieved using an Invitrogen Purelink Genomic DNA Kit. XPD alleles of Lys751Gln (rs13181) and XPG Asp1104His (rs17655) loci from genomic DNA samples were reproduced using polymerase chain reaction. A statistically significant difference in XPD genotype distribution between control and patient groups was determined (P=0.019). XPD Lys+ was significantly more common in the patient group than in the control group, and a two-fold increased risk for disease was determined. XPD Gln/Gln+ was significantly more common in the control group than in the patient group, and a two-fold decrease in risk for disease was determined (P=0.045). In the other region of the study, there was no statistically significant difference in terms of disease development between XPG genotypes. In conclusion, Lys751Gln polymorphism in the XPD gene could play a role in oral squamous cell development. It is important to increase the numbers of subjects in patient groups and healthy controls in studies to increase the possibility of determining XPD’s potential as a molecular risk factor.